Foreign banks' attraction to the financial centre Frankfurt - a 'u'-shaped relationship - Michael H. Grote (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2007)
This paper traces the location of foreign banks in Germany from 1949 to 2006. As suggested by new economic geography models we find a 'u'-shaped concentration of foreign banks in Germany. Only after a competition between several cities, Frankfurt has emerged as the pre-eminent financial centre, triggered by the 'historical event' of setting up the German central bank in Frankfurt. After a strong increase, Frankfurt's share in the location of foreign banks in Germany decreases slowly but significantly since the mid 1980's. We conclude that there will be a lesser role in Europe for secondtier financial centres in the future.
Keywords: N94; R11; 330; financial centres; "u"-shape; foreign banks; Frankfurt; Internationale Bank; Standortwahl; Finanzplatz; Deutschland; Frankfurt (Main)